Mitochondrial Degeneration and Autophagy Associated With Delayed Effects of Radiation in the Mouse Brain - Sharma, Neel K.; Stone, Sasha; Kumar, Vidya P.; Biswas, Shukla; Aghdam, Saeed Y.; Holmes-Hampton, Gregory P.; Fam, Christine M.; Cox, George N.; Ghosh, Sanchita P. (Frontiers in Aging Neuroscience, 2019)
Mitochondria are linked with various radiation responses, including mitophagy, genomic instability, apoptosis, and the bystander effect. Mitochondria play an important role in preserving cellular homeostasis during stress responses, and dysfunction in mitochondrial contributes to aging, carcinogenesis and neurologic diseases. In this study, we have investigated the mitochondrial degeneration and autophagy in the hippocampal region of brains from mice administered with BBT-059, a long-acting interleukin-11 analog, or its formulation buffer 24 h prior to irradiation at different radiation doses collected at 6 and 12 months post-irradiation. The results demonstrated a higher number of degenerating mitochondria in 12 Gy BBT-059 treated mice after 6 months and 11.5 Gy BBT-059 treated mice after 12 months as compared to the age-matched naïve (non-irradiated control animals). Apg5l, Lc3b and Sqstm1 markers were used to analyze the autophagy in the brain, however only the Sqstm1 marker exhibited significantly reduced expression after 12 months in 11.5 Gy BBT-059 treated mice as compared to naïve. Immunohistochemistry (IHC) results of Bcl2 also demonstrated a decrease in expression after 12 months in 11.5 Gy BBT-059 treated mice as compared to other groups. In conclusion, our results demonstrated that higher doses of ionizing radiation (IR) can cause persistent upregulation of mitochondrial degeneration. Reduced levels of Sqstm1 and Bcl2 can lead to intensive autophagy which can lead to degradation of cellular structure.